Gambaran Pengetahuan Menyikat Gigi Dan Keadaan Karang Gigi Pada Siswa Sekolah Dasar - Ria Nurmalina; Dwi Suyatmi; Etty Yuniarly (Journal of Oral Health Care, 2017)
The knowledge was the outcome of ‘knew’, and happened after someone did the sense of the object. The sense that happened through five sensory of human, such as sight sensory, heard sensory, smelled sensory, tasted, and touched. Human knowledge is developed through eyes and ears. Tooth brushing was the activity to clear plaque and the remnants of provisions. The doctors suggested brushing the teeth twice a day after breakfast and dinner before sleep. The minimal tooth brushing is two minutes, using toothpaste that contained fluoride. The calculus was the solid sediment located on the surfaces of the teeth and colored from yellowish, brownish, until blackish and had the rough surfaces. The aims of this research were to investigate the knowledge of tooth brushing and the conditions of calculus from the elementary student. This research was descriptive with a cross-sectional design. The location of this research in Pundong Elementary School, Tirtoadi, Mlati, Sleman. As the sample, this research used student in 4th and 5th grade of Pundong Elementary School, Tirtoadi, Mlati, Sleman that taken using Jenuh sample. The result showed that the knowledge of tooth brushing of students at middle criteria as much as 90,2 %. And the calculus showed nothing at students as much as 54, 9% and the criteria of there was calculus as much as 45,1%. The knowledge of tooth brushing in middle criteria at the calculus criteria nothing calculus as much as 49,1%